3D-printing zirconia implants; a dream or a reality? An in-vitro study evaluating the dimensional accuracy, surface topography and mechanical properties of printed zirconia implant and discs. (November 2017) - Osman, Reham B.; van der Veen, Albert J.; Huiberts, Dennis; Wismeijer, Daniel; Alharbi, Nawal
Abstract: Purpose: The aim of this study was to evaluate the dimensional accuracy, surface topography of a custom designed, 3D-printed zirconia dental implant and the mechanical properties of printed zirconia discs. Materials and methods: A custom designed implant was 3D-printed in zirconia using digital light processing technique (DLP). The dimensional accuracy was assessed using the digital-subtraction technique. The mechanical properties were evaluated using biaxial flexure strength test. Three different build angles were adopted to print the specimens for the mechanical test; 0°(V ertical), 45° (O blique) and 90°(Horizontal) angles. The surface topography, crystallographic phase structure and surface roughness were evaluated using scanning electron microscopy analysis (SEM), X-ray diffractometer and confocal microscopy respectively. Results: The printed implant was dimensionally accurate with a root mean square (RMSE) value of 0.1 mm. The Weibull analysis revealed a statistically significant higher characteristic strength (1006.6 MPa) of 0° printed specimens compared to the other two groups and no significant difference between 45° (892.2 MPa) and 90° (866.7 MPa) build angles. SEM analysis revealed cracks, micro-porosities and interconnected pores ranging in size from 196 nm to 3.3 µm. The mean Ra (arithmetic mean roughness) value of 1.59 µm (±0.41) and Rq (root mean squared roughness) value of 1.94 µm (±0.47) was found. A crystallographic phase of primarily tetragonal zirconia typical of sintered Yttria tetragonal stabilized zirconia (Y-TZP) was detected. Conclusions: DLP prove to be efficient for printing customized zirconia dental implants with sufficient dimensional accuracy. The mechanical properties showed flexure strength close to those of conventionally produced ceramics. Optimization of the 3D-printing process parameters is still needed to improve the microstructure of the printed objects. Graphical abstract: fx1 Highlights: Custom designed zirconia dental implants can be printed using digital light processing with sufficient dimensional accuracy. The flexural strength of the printed material was comparable to those of conventionally milled zirconia. Optimization of the AM process parameters is still needed to improve the microstructure of the printed objects.